INTEGRATION PREFERENCE AS MODERATORS OF THE RELATIONSHIP BETWEEN WORK-RELATED ICT USE OUTSIDE WORK HOURS AND WORK-FAMILY ENRICHMENT - Ahmad, Azimah; Zakaria, Mohd Nazri (International Journal of Accounting, Finance and Business, 2024)
Modern workplace demands cause employees to engage in work, even without written contractual obligations. The advancement in digital technology encourages an “always on” culture, blurring the line between work and family life. The recent COVID-19 pandemic has forced the use of mobile technology to perform work tasks among employees. Still, relatively little research has examined whether work-related ICT use outside work hours may help individuals benefit from multiple roles. This study investigated the effect of work-related ICT use outside work hours (WRICT) and work-family enrichment (WFE) experienced by non-academic employees in Malaysia. Specifically, the moderating roles of integration preference were considered in investigating the relationship between work-related ICT use outside work hours on WFE. A quantitative research approach was adopted, and an online survey was used to collect data. The sample consisted of non-academics from a public university in Malaysia (n = 690). Two statistical programs were used for the data analysis: Analysis of Moment Structures (AMOS) and Statistical Package for the Social Sciences (SPSS). The research revealed a positive effect between work-related ICT use outside work hours and WFE. Furthermore, the results showed that integration preference significantly moderated the relationship between WRICT and WFE. This study contributes to the literature on growing challenges in the work-family interface by demonstrating how work-related ICT use outside work hours (WRICT) impacts work-family enrichment (WFE). These findings suggest that for integrators, ICT use outside work hours may be favourable to meet both work and family roles, which has the potential to experience more work–family enrichment.